A Pseudo-Ligand Approach to Virtual Screening - Schuller, Andreas; Fechner, Uli; Renner, Steffen; Franke, Lutz; Weber, Lutz; Schneider, Gisbert (Combinatorial Chemistry & High Throughput Screening, 2006)
A virtual screening method is presented that is grounded on a receptor-derived pharmacophore model termed
Keywords: pharmacophore